Control of Piston Trajectory in a Free-Piston Linear Electric Generator by Load Current Modulation - Bashir, A. (Institute of Electrical and Electronics Engineers Inc., 2020)
A free-piston engine (FPE) is a linearly-reciprocating internal combustion engine (ICE) which offers many advantages over the conventional crank-slider ICE. Benefits include improved thermal and mechanical efficiencies, multiple fuel capability due to the free-piston dynamics and variable compression ratio, and higher power-to-weight ratio due to single-moving part and compact design. Coupled to a linear electric generator (LG), the resultant system is a free-piston linear electric generator (FPLG)-an alternative power source for vehicle propulsion and portable power generation. This paper discusses control issues of the FPLG and proposes an electrical solution to achieve sustained operation in the face of combustion variation and engine misfires. It presents simulation results on the effect of varying output load current on piston trajectory, for viability of automatic control in an otherwise unconstrained FPLG. Â© 2020 IEEE.